2011
DOI: 10.1007/s00198-010-1503-z
|View full text |Cite
|
Sign up to set email alerts
|

A critical review of racial/ethnic variables in osteoporosis and bone density research

Abstract: This analysis indicates that more rigorous examination of what race/ethnicity actually captures, more careful definitions of group labels and the procedures for assigning them, and attention to the limitations of how such variables can reliably be used in data analyses is needed to help address the problems and issues outlined in this review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 40 publications
0
28
0
Order By: Relevance
“…Internationally, previous studies show that demographic and socio-economic characteristics affect the prevalence of the elderly fall (Andersen 2008;Cakar et al 2011;Cauley 2011;Dhanwal et al 2011;Galizia et al 2008;Graham et al 2008;Haan et al 1987;Hokby et al 2003;Jacobsen et al 1992;Kannus et al 1999;Landi et al 2001;Lopata 1982;Luukinen et al 1996;Megyesi et al 2011;Nguyen-Oghalai et al 2009;Penrod et al 2008;Reimers and Laflamme 2007;Sandberg et al 2012;Tinetti et al 1988;Trujillo et al 2011;Van Rossum et al 2000). Based on this literature, it is suggested that counties that have higher rates of falls are expected to be associated with one or more of these factors: lower proportion of nonSwedes, greater proportion of non-active population, larger share of low income earners, and single individuals.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 91%
See 1 more Smart Citation
“…Internationally, previous studies show that demographic and socio-economic characteristics affect the prevalence of the elderly fall (Andersen 2008;Cakar et al 2011;Cauley 2011;Dhanwal et al 2011;Galizia et al 2008;Graham et al 2008;Haan et al 1987;Hokby et al 2003;Jacobsen et al 1992;Kannus et al 1999;Landi et al 2001;Lopata 1982;Luukinen et al 1996;Megyesi et al 2011;Nguyen-Oghalai et al 2009;Penrod et al 2008;Reimers and Laflamme 2007;Sandberg et al 2012;Tinetti et al 1988;Trujillo et al 2011;Van Rossum et al 2000). Based on this literature, it is suggested that counties that have higher rates of falls are expected to be associated with one or more of these factors: lower proportion of nonSwedes, greater proportion of non-active population, larger share of low income earners, and single individuals.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 91%
“…This ethnic and geographic variation may be explained by differences in genetic factors, lifestyle, behavioral, and environmental characteristics (Dhanwal et al 2010). The relationship between fall incidents and ethnical variations has been reported in a number of studies (Cauley 2011;Megyesi et al 2011;Jacobsen et al 1992;Penrod et al 2008;Graham et al 2008;Nguyen-Oghalai et al 2009;Dhanwal et al 2011). The income of the individual may be another important factor suggested by scholars as an implication for fall-related injuries (Kannus et al 1999;Tinetti et al 1988;Galizia et al 2008;Luukinen et al 1996).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 91%
“…Many studies have shown that there exists substantial difference in BMD among different ethnic groups and even within a group of the same ethnic origin [135][136][137][138][139]. For example, black men have greater BMD than Hispanic or white men.…”
Section: Racementioning
confidence: 97%
“…Assessment of ethnic differences in BMD has recently been the subject of some controversy [26,27]. The strengths of our study include detailed body composition assessment as well as hip and spine BMD measurement.…”
Section: Indigenous Men and Women In This Study Our Finding Of Highementioning
confidence: 99%